Pengaruh Kompensasi terhadap Kinerja Karyawan dalam Perusahaan - Prabowo, Budi; Samsudin, Acep; Rahim, Muhammad Auliya; Kurniawan, Bima Wahyu; Nurtalia, Athaillah Cindra (Ikatan Da'i Indonesia, 2024)
Compensation is a key element in human resource management that has a significant impact on employee performance in the company. Fair pay and financial motivation have long been topics of deep research in a variety of disciplines, including management, economics, and psychology. Compensation has a role in helping employees perform better. Employee performance will be influenced by compensation, so to ensure that workers work professionally, organizations must consult with them to decide on compensation levels. Business effectiveness and efficiency will be influenced by the quality of human resources, which will be determined by success in determining appropriate compensation for employees. This journal uses the library research or literature review method as the main basis in the process of writing scientific articles or journals. The reference sources used in this article were obtained through Google Scholar, a platform that facilitates access to various sources of scientific literature. In this way, we can ensure that this scientific article is supported by quality and relevant sources. The implications of this research indicate that companies should consider these factors in the planning and implementation of their human resource policies to achieve optimal employee performance and ensure employee well-being. Thus, these aspects can serve as guidelines in improving human resource management in organizations.